The effectiveness of major ozone autohemotherapy in the treatment of fibromyalgia syndrome: Major ozone autohemotherapy in the treatment of fibromyalgia - Ahi, Emine Dundar; Afsar, Sevgi Ikbali (Journal of Surgery and Medicine, 2022)
Background/Aim: Fibromyalgia syndrome (FMS) is a disease that seriously affects the quality of life. Although many modalities are used in treatment, there is still no common protocol. The aim of this study was to evaluate the effectiveness of major autohemotherapy (MAH) with ozone, which has come into use in recent years. Methods: The retrospective cohort study included 45 male and female patients who were admitted to the Physical Medicine and Rehabilitation (PMR) outpatient clinic of Private Medar Hospital between January 2017 and October 2020 and were treated with MAH for a diagnosis of FMS. Evaluations were made before and after the last session of treatment using a visual analog scale (VAS), the Fibromyalgia Impact Questionnaire (FIQ) and the Short Form Health Survey-36 (SF-36). The scores of the patients were compared. Results: Posttreatment VAS and FIQ scores decreased significantly (P = 0.014, P = 0.022 respectively) compared to pretreatment. After treatment, SF-36; PF, PH, EP, Fatigue, EW, SF, Pain, GH, HC scores increased significantly (P < 0.05 for all) compared to before treatment. The use of analgesics after treatment decreased significantly (P = 0.033) compared to before treatment. Conclusion: MAH applied twice a week is an effective and practical method in the treatment of FMS.